Evaluating the performance of the Agricultural Cooperative Bank in Lattakia (Latakia University Journal -Biological Sciences Series, 2020)
This study was conducted to analyze the loans provided by the Agricultural Cooperative Bank in Lattakia during the period 2008-2018 in order to clarify the relative importance of providing  loans according to their terms (short, medium, and long-term). The results showed a decrease 12.5% of the young age group benefiting from the loans,  in the recent years, Agricultural Cooperative Bank worked to grant short and medium-term loans and not long-term, thus the limited role of these loans in developing the agricultural sector, as the results showed that the annual growth rate of the total loans provided by the Agricultural Cooperative Bank in Lattakia Governorate reached 32.46% during the study period, and the short and medium-term loans values has taken an increasing general trend with an annual increase, with a growth rate 25, 56.8 % respectively during the studied period, the study recommended the need to amend mechanism of investing financial resources available in the Agricultural Bank in order to reduce short-term loans volume to increase long-term loans volume as they play important role in the agricultural development process, in addition, to provide facilities and overcome obstacles to obtaining loans.